Pengaruh Perceived Organizational Support Terhadap Kinerja Melalui Budaya Organisasi - agustini, agustini; Adolf, Bastian; Afriana, Munthe Richa (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2025)
The purpose of this study was to determine the effect of Perceived organizational support on the performance of employees of the Rokan Hilir Regency Education Office mediated by organizational culture. The population in this study were all employees of the Rokan Hilir Regency Education Office totaling 66 people where sampling was carried out using the saturated sampling method. The data collection technique used a questionnaire and distribution using a google form. The data analysis technique in this study used Structural Equation Modeling (SEM) using SmartPLS 3.0 as a data processing tool. The results of this study indicate that Perceived organizational support has a positive effect on employee performance, organizational culture has a positive effect on employee performance, and Perceived organizational support also has a positive effect on organizational culture. The results of the mediation test also show that organizational culture is able to mediate the effect of Perceived organizational support on employee performance at the Rokan Hilir Regency Education Office. This means that when employees feel supported by the organization, this will form a positive organizational culture (for example, a culture of mutual support, openness, and productivity). This positive organizational culture then contributes to improving employee performance